Teachers' Multimodal Literacy in Practice: Investigating Pedagogical Decision-Making in the Design of English Lesson Plans - Tria Amelia Kartika Dewi; Novia Trisanti (Universitas Islam Negeri Palopo, 2026)
Multimodal literacy has become an essential component of twenty-first-century English language teaching; however, previous research has predominantly examined it through classroom implementation, with limited attention to its representation in instructional planning. Addressing this gap, this study investigated how multimodal literacy was represented in English lesson plans developed by teachers at an Indonesian secondary school implementing the Merdeka Curriculum. Employing Qualitative Document Analysis, three English lesson plans were analyzed through within-case and cross-case comparisons to identify recurring pedagogical patterns. The findings revealed four major themes. First, multimodal literacy remained implicit within learning outcomes and objectives despite being reflected in instructional design. Second, teachers consistently integrated multimodal resources across instructional components. Third, student-centered learning activities incorporated multiple modes of communication that encouraged collaboration and active meaning-making. Fourth, assessment practices continued to focus primarily on language competence, indicating that multimodal literacy was not yet systematically represented across all components of lesson plans. Collectively, these findings suggest that multimodal literacy had not yet achieved constructive alignment among intended learning outcomes, teaching and learning activities, and assessment. This study contributes to multimodal literacy research by positioning English lesson plans as pedagogical evidence of teachers' instructional decision-making rather than focusing solely on classroom implementation. The findings also provide practical implications for English teachers and curriculum developers in designing lesson plans that explicitly align multimodal learning outcomes, instructional activities, and assessment to strengthen the implementation of multimodal literacy within the Merdeka Curriculum.